Opposite clozapine and ziprasidone effects on the reactivity of plasma albumin SH-group are the consequence of their different binding properties dependent on protein fatty acids content. (25th September 2019) - Uzelac, Tamara N.; Nikolić-Kokić, Aleksandra L.; Spasić, Snežana D.; Mačvanin, Mirjana T.; Nikolić, Milan R.; Mandić, Ljuba M.; Jovanović, Vesna B.
Abstract: Antipsychotic drugs interfere with the antioxidant defense system provoking complex and often toxicological effects. Here we examined differences in plasma albumin reduced free thiol (SH) group content and its reactivity as a consequence of clozapine (CLZ) and ziprasidone (ZIP) binding. Chronic administration of CLZ reduced, whereas treatment with ZIP increased albumin-SH content in rats. Regardless of the ratio of stearic acid (SA) bound to protein, in vitro binding of ZIP to human serum albumin (HSA) increased both the SH group level and reactivity. In contrast, the effect of CLZ on HSA-SH reactivity was dependent on HSA to SA molar ratio. CLZ binding was accompanied by an increase in HSA-SH reactivity in samples with normal, but a reduction of its reactivity level with higher SA/HSA ratio, compared to drug-free samples. We demonstrate by steady-state fluorescence quenching studies that an increase in SA binding to HSA is associated with a significant reduction of binding constant for both antipsychotics. In addition, this is the first report of quantitative characterization of ZIP binding to HSA. Our findings suggest that albumin-SH content and reactivity is modulated by ZIP towards an increased antioxidant defense capacity in circulation, as opposed to CLZ, which can contribute to the safer, more effective treatment of schizophrenia. Graphical abstract: Image 1 Highlights: Clozapine decreases, while ziprasidone increases free albumin-SH fraction in rats. In vitro drug effects on HSA-SH level/reactivity depend on stearic acid content. Observed effects are associated with differences in drugs binding to (de)fatted HSA.